2019
DOI: 10.1177/1468087419879530
|View full text |Cite
|
Sign up to set email alerts
|

A study of suspension plasma-sprayed insulated pistons evaluated in a heavy-duty diesel engine

Abstract: Thermal barrier coatings can be used to reduce the heat losses in heavy-duty diesel engines. A relatively new coating method for thermal barrier coatings is suspension plasma-spraying. Single-cylinder engine tests have been run to evaluate how heat losses to piston, cylinder head and exhausts as well as the specific fuel consumption are influenced by coating pistons with two different suspension plasma-sprayed thermal barrier coatings and one atmospheric plasma-sprayed thermal barrier coating, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…The SiRPA coating was reported to give small improvements in thermal efficiency (< 2 %) and exhaust gas temperatures while reducing the energy transferred to the coolant. Similar coatings have been tested by various researchers, where similar improvements, albeit small, were observed [7,8,[10][11][12] with some researchers however, reporting a deterioration in fuel consumption when these coating where employed [13].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The SiRPA coating was reported to give small improvements in thermal efficiency (< 2 %) and exhaust gas temperatures while reducing the energy transferred to the coolant. Similar coatings have been tested by various researchers, where similar improvements, albeit small, were observed [7,8,[10][11][12] with some researchers however, reporting a deterioration in fuel consumption when these coating where employed [13].…”
Section: Introductionsupporting
confidence: 66%
“…It has been shown that the surface roughness [8] and the permeable porosity [10,13] can have an adverse effect on the expected gains in efficiency. An increase in surface roughness has the potential to increase heat transfer losses due to a higher surface area [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several other studies have been conducted to determine the impact of insulating the combustion chamber walls of an ICE. 20,21 Developing new coating materials for ICEs is quite challenging as they have to combine optimal insulating properties with resistance and adherence properties to endure the engine operating conditions. Advanced test benches and numerical simulations are needed in order to determine the effectiveness of the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several other studies have been conducted to determine the impact of insulating the combustion chamber walls of an ICE. 20,21…”
Section: Introductionmentioning
confidence: 99%